A rapid detection method for the residual amount of polyaluminum flocculant in machine-made sand
By detecting the content of aluminum ions in the machined sand, the problem of the inability to quickly detect polyaluminum flocculants in the existing technology is solved, and the rapid and accurate detection of polyaluminum flocculants is achieved, and the quality control and production efficiency of concrete are improved. .
Patent Information
- Application Number
- CN202211025654.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-25
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-08-25
AI Technical Summary
The prior art cannot quickly and effectively detect the impact of the residual polyaluminum flocculant in machined sand on the concrete performance, resulting in large amount of water consumption, high admixture dosage, and construction and quality problems.
By preparing the solution to be tested, establishing a standard curve, and using an ultraviolet spectrophotometer to detect the content of aluminum ions in the machined sand, a color-developing complex is generated, and the content of aluminum ions is calculated, thereby quickly detecting the residual polyaluminum flocculant in the sand Dosage.
The rapid and accurate detection of polyaluminum type flocculants in machined sand is achieved, which reduces the inspection cost, simplifies the operation process, improves the quality control of concrete raw materials, and reduces production costs.
Smart Images

Figure CN115436122B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a method for testing and analyzing the residual amount of polyaluminum type flocculant in machine-made sand. Background Art
[0002] Flocculants are mainly groups with positive (negative) charges and some negative (positive) charged particles or granules in water that are difficult to separate, which brings them closer to each other, lowering their electric potential and making them unstable. They also use their aggregation properties to concentrate these particles and separate them through physical or chemical methods.
[0003] Aggregates of sand and gravel are the main raw materials for structures such as concrete and masonry in construction facilities. In recent years, with the vigorous development of the construction industry, the production scale and output of aggregates of sand and gravel have been constantly refreshed. Artificial sand is the most widely used aggregate product of sand and gravel at present. Most manufacturers of artificial sand use wet process to produce artificial sand. Since a large amount of wastewater will be generated during the cleaning process of artificial sand, in order to reduce wastewater discharge and improve water utilization, many sand and gravel manufacturers use flocculants in the sewage treatment process to accelerate the sedimentation of particles in the wastewater and realize the recycling of wastewater. However, since the surface of sand and gravel contains a large number of hydroxyl groups, flocculants are easily adsorbed and remain on the surface of artificial sand during the recycling process of wastewater. A small amount of flocculants can improve the workability of concrete, but when the amount of flocculants in concrete is excessive, it will have a serious impact on the workability of concrete. According to actual engineering application reports, the use of sand and gravel containing flocculants leads to large water consumption, high admixture dosage, and rapid concrete loss, which induces construction and quality problems. Studies have shown that when the concentration of polyaluminium chloride exceeds 0.02%, it has a significant impact on the amount of water reducer and concrete strength, greatly increasing the production cost and quality control of commercial concrete mixing plants. Therefore, the content of flocculant in sand is crucial to the performance of concrete construction.
[0004] At present, flocculants used in water treatment are mainly divided into two categories: inorganic flocculants and organic polymer flocculants. Inorganic polymer flocculants are mainly aluminum salt polymers, such as polyaluminum chloride, polyaluminum sulfate, etc. This polyaluminum type flocculant is widely used in drinking water, industrial water, sand and gravel wastewater treatment and industrial wastewater treatment due to its fast precipitation speed, wide applicable pH range, non-corrosiveness to pipeline equipment, and obvious water purification effect.
[0005] For the concrete industry, the demand for machine-made sand is large and the sources are complex, but the current flocculant detection method cannot achieve the purpose of rapid and effective detection, and it is also impossible to determine how much impact the residual flocculant in the sand will have on the performance of concrete. A small amount of flocculant is beneficial to improve the working performance of concrete, but an excessive amount of flocculant will seriously affect the working performance of concrete. Therefore, how to quickly determine whether the flocculant content in concrete sand is excessive is a technical problem to be solved in this field.
[0006] Patent CN 113030447 A discloses a method for detecting polyacrylamide in machine-made sand. The patent uses expansion as a link to associate flocculant content with expansion, and compares the changes in water-reducing agent dosage after the machine-made sand reaches the same expansion. However, this method is mainly used for polyacrylamide flocculants and ignores the fact that polyacrylamide at low concentrations can effectively improve the workability of concrete without affecting the water-reducing agent dosage. Patent CN 110261265 A discloses a method for detecting flocculants in sand and its detection device. The patent establishes a flocculant content and viscosity curve to detect the residual flocculant content in machine-made sand. However, this method does not take into account the hydrolysis characteristics of polyacrylamide, and the viscosity decreases significantly after hydrolysis, but can still induce the characteristics of high water-reducing agent dosage and fast loss in concrete. In summary, the current flocculant detection method focuses on solving the detection of organic polymer flocculants in sand, ignoring the impact of residual polyaluminum flocculants in machine-made sand on concrete, and cannot fundamentally achieve the purpose of rapid and effective detection of residual flocculants in machine-made sand. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention aims to provide a detection and analysis method for polyaluminum flocculants in machine-made sand, so as to accurately, quickly and easily detect the dosage of polyaluminum flocculants in machine-made sand, effectively enhance the risk prevention and control awareness of raw materials in mixing stations and improve the quality of concrete.
[0008] The above technical objectives of the present invention are achieved through the following technical solutions:
[0009] A rapid detection method for the residual amount of polyaluminum type flocculant in machine-made sand comprises the following detection steps:
[0010] 1. Preparation of test solution
[0011] The machine-made sand sample is dried, deionized water is added and stirred to make it completely wetted, and then sodium hydroxide is added, the temperature is raised to 60-100°C and boiled for 1-2 hours, and sodium hydroxide is added to boil until the solution has no white flocs, then cooled to room temperature. After centrifugation, filtration, and multiple washings, the filtrate is taken out and inorganic acid is added until the solution becomes transparent, and then water is added to dilute the volume to obtain the test solution.
[0012] 2. Establish a standard curve
[0013] S1. Weigh different masses of standard aluminum solution into a conical flask, add acid-base indicator and inorganic acid to adjust the pH to acidic, then add buffer solution, emulsifying solution, masking agent, and color developer, dilute to 50 mL with water, mix well, heat to boil, and then cool to room temperature.
[0014] S2. Introduce the standard aluminum solution treated by S1 into the UV spectrophotometer through the sampling system for testing, measure the absorbance of the solution with the actual blank as a reference, and draw a standard curve of aluminum content and absorbance.
[0015] S3. Based on the standard curve of aluminum content and absorbance drawn in S2, establish the standard curve equation.
[0016] 3. Test sample solution
[0017] S1. Weigh the sample solution to be tested into a conical flask, add acid-base indicator and inorganic acid to adjust the pH to acidic, then add buffer solution, emulsifying solution, masking agent, and color developer, dilute to 50mL with water, mix well, heat to boil, and then cool to room temperature.
[0018] S2. Introduce the polyaluminium solution sample to be tested into the UV spectrophotometer through the sampling system for testing, substitute the absorbance of the polyaluminium solution sample to be tested into the standard curve equation established in step 2 S3, and calculate the aluminium content in the sample to be tested.
[0019] Furthermore, the inorganic acid selected in the polyaluminium solution is one of sulfuric acid, nitric acid and hydrochloric acid or a mixture of two or more in any proportion, and the inorganic acid solution is configured to have a concentration of 10 mol / L.
[0020] Furthermore, the acid-base indicator is a p-nitrophenol solution (1 g / L), which is prepared according to the following process: 0.1 g of p-nitrophenol is weighed and dissolved in 20 g of deionized water, and the solution is diluted to a constant volume of 100 ml.
[0021] Furthermore, the buffer solution is mainly composed of one or two of sodium acetate-acetic acid or ammonium acetate-acetic acid.
[0022] Furthermore, the emulsified solution is composed of one or more of OP-3, OP-10 and lauryl alcohol polyoxyethylene ether, and the added amount thereof is 0.1% to 3% of the total mass.
[0023] Furthermore, the masking agent is one or more of ascorbic acid, citric acid, mandelic acid, and o-phenanthroline, and the preparation steps are to accurately weigh the masking agent and prepare a masking agent solution with a concentration of 50 g / L by constant volume with deionized water.
[0024] Furthermore, the main component of the developer is aluminum reagent, i.e., tricarboxyammonium salt of golden yellow pigment, with a molecular formula of C22H23N3O9. The preparation of the developer comprises the following steps: accurately weighing aluminum reagent, gum arabic, ammonium acetate and acetic acid solution, transferring them into a volumetric flask, and making up to a concentration of 0.5 g / L aluminum reagent solution with deionized water.
[0025] Furthermore, the detection wavelength under the ultraviolet spectrophotometer is 400-600 nm, and more preferably 500-540 nm.
[0026] The standard curve in the above steps is drawn by detecting multiple standard sample solutions with different contents within the linear range by ultraviolet spectrophotometry, with aluminum content (ug) as the horizontal coordinate and absorbance as the vertical coordinate. The regression equation is calculated by the obtained standard curve according to the Lambert-Beer law.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The present invention treats the machine-made sand reagent solution to be tested by alkalization, acidification and other treatment methods, so that the aluminum ions in the polyaluminum flocculant in the sand react with the reagent to form a color complex, and the content of aluminum ions is calculated by detecting the absorbance, thereby achieving the purpose of detecting the amount of residual polyaluminum flocculant in the sand. The present invention uses a spectrophotometer method, which is lower in cost and simple to operate than inductively coupled plasma mass spectrometry (ICP-MS) and inductively coupled plasma emission spectrometer (ICP-OES), and can quickly obtain the residual flocculant content in the machine-made sand.
[0029] (2) The present invention directly alkalizes and acidifies the machine-made sand solution containing the polyaluminum type flocculant, which can save the time and economic costs of direct washing followed by rotary evaporation concentration. In addition, by determining the temperature and time of the alkalization and acidification process by itself, the influence of the reaction between silicon dioxide and sodium hydroxide on the test results can be avoided.
[0030] (3) The use of emulsifiers and buffers improves the coordination reaction efficiency between aluminum ions and color developers, shortens the color development time, and can improve the efficiency of detection and analysis to a certain extent.
[0031] (4) The present invention detects the content of polyaluminum-type flocculants in residual flocculants in machine-made sand, which is based on early research on problems such as polyaluminum-type flocculants inducing concrete machine loss, high proportion of admixture slump-preserving components, and low 28-day strength retention rate. The detection of polyaluminum-type flocculants in machine-made sand is conducive to the quality control of concrete raw materials, improving the quality of concrete, and promoting industry progress.
[0032] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 The aluminum content-absorbance standard curve established by the present invention is based on a spectrophotometer.
[0035] Figure 2 The present invention uses a large precision instrument ICP-OES as the aluminum content-absorbance standard curve for comparison of the method of the present invention. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The present invention is further explained below in conjunction with specific embodiments. Preparation of standard aluminum solution: Weigh 0.0139 g of aluminum nitrate nonahydrate, dissolve it with deionized water, and dilute it to a 50 mL volumetric flask. Then transfer 10 mL to a 100 mL volumetric flask and dilute it to the mark with deionized water. The concentration of the standard aluminum solution is 2 mg / L.
[0038] Establishment of standard curve (ultraviolet spectrophotometry): Pipette a certain amount of standard aluminum ion concentration, add 5 drops of acid-base indicator, then add 1 mL of inorganic acid solution, add 10 mL of buffer solution, continue to add 1 mL of masking agent solution, add 0.5 mL of surfactant solution, add 2 mL of color developer solution, dilute to 50 mL, and prepare standard colorimetric solutions with aluminum content of 0, 5, 10, 15, 20, 40, 60, 80, 120, 160 μg. Heat and boil the standard colorimetric solution for 15 minutes and then cool to room temperature. Test the absorbance at a wavelength of 520 nm using an ultraviolet spectrophotometer. Establish a standard curve with absorbance and aluminum content. The equation of the standard curve is: Y = 0.00433*X + 0.10575, R2 = 0.999.
[0039] Establishment of standard curve (ICP-OES): Pipette a certain amount of standard aluminum ion concentration, add 0.5 mL of inorganic acid solution and make the volume to 50 mL, prepare standard solutions with aluminum content of 0, 5, 10, 15, 20, 40, 60, 80, 120, and 160 μg, test under the 308.215 nm characteristic spectrum of ICP-OES, establish a standard curve with aluminum content and absorbance, and the standard curve equation is: Y=2414.89*X+0151.89, R2=0.999.
[0040] Comparative Example 1
[0041] Preparation of polyaluminium solution: weigh 1g of polyaluminium sulfate and 100g of water and put them into a three-necked flask with a stirring device, add 5g of sodium hydroxide and heat to 60°C, cook for 1.0h, add 0.5g of sodium hydroxide and continue to cook for 0.5h. After adding 0.1g of sodium hydroxide, no white flocs appear, and the cooking process is over. After cooling to room temperature, filter and take out the filtrate, add 25g of hydrochloric acid solution to the filtrate twice, stir for 20min, cool to room temperature and make up to 500mL.
[0042] Aluminum content test of polyaluminum solution:
[0043] (1) Spectrophotometer method:
[0044] Pipette 5 mL of polyaluminum solution, add 5 drops of acid-base indicator, then add 1 mL of inorganic acid solution, add 10 mL of buffer solution, continue to add 1 mL of masking agent solution, add 0.5 mL of surfactant solution, add 2 mL of color developer solution, make up to 50 mL, heat and boil for 15 minutes, then cool to room temperature, test the absorbance at a wavelength of 520 nm on a UV spectrophotometer, substitute it into the standard curve of the spectrophotometer test, and calculate the aluminum content.
[0045] (2) ICP-OES method:
[0046] 5 mL of polyaluminum solution was transferred, 0.5 mL of nitric acid solution was added and the volume was made up to 50 mL. The solution was tested under the 308.215 nm characteristic spectrum of ICP-OES. The tested intensity value was substituted into the standard curve obtained by ICP-OES to calculate the aluminum content.
[0047] Spiked recovery test: Pipette 5 mL of polyaluminum solution and 0.5 mL of standard aluminum solution, add 5 drops of acid-base indicator, then add 1 mL of inorganic acid solution, add 10 mL of buffer solution, continue to add 1 mL of masking agent solution, add 0.5 mL of surfactant solution, add 2 mL of color developer solution, make up to 50 mL, heat and boil for 15 minutes, then cool to room temperature, test the absorbance at a wavelength of 520 nm on a UV spectrophotometer, substitute it into the standard curve of the spectrophotometer test, and calculate the aluminum content and spike recovery.
[0048] Example 1
[0049] Weigh 100g of standard sand and 1g of polyaluminium chloride in a four-necked flask, add deionized water and stir for 20 minutes, then add 5g of sodium hydroxide and heat to 60°C, boil for 1.0h, add 0.1g of sodium hydroxide and continue boiling for 0.5h, cool to room temperature, filter and wash, take out the filtrate, add 25g of hydrochloric acid solution twice, stir for 20 minutes, cool to room temperature and adjust the volume to 500mL. According to the spectrophotometer method and ICP-OES method in the comparative example, substitute them into the standard curve to calculate the aluminum content.
[0050] Example 2
[0051] The artificial sand used in the production of a concrete company in Sichuan was selected for analysis of residual polyaluminum flocculant. When the company used the artificial sand to produce concrete, the dosage of admixture increased from the original 2.0% to 3.0%, and the concrete showed problems such as rapid loss.
[0052] Take 300g of the machine-made sand, dry it, weigh 100g, put it in a four-necked flask, add 50g of deionized water, stir for 20 minutes, add 3.0g of sodium hydroxide, heat it to 70℃ and cook it for 1.5 hours, add 1.0g of sodium hydroxide and continue to cook it until there is no white floccules, then cool it to room temperature, centrifuge, filter, and wash it multiple times, take out the centrifuge liquid, filter and wash it, take out the filtrate and gradually add nitric acid until the solution is transparent, then make the volume to 100mL for standby use, and obtain the polyaluminum solution to be tested.
[0053] Take 10 mL of the polyaluminum solution to be tested, add 5 drops of acid-base indicator, then add 1 mL of inorganic acid solution, add 10 mL of buffer solution, continue to add 1 mL of masking agent solution, add 0.5 mL of surfactant solution, add 2 mL of color developer solution, make the volume to 50 mL, heat and boil for 15 minutes, then cool to room temperature, test the absorbance at a wavelength of 520 nm on a UV spectrophotometer, substitute it into the standard curve of the spectrophotometer test, and calculate the aluminum content.
[0054] Take 10 mL of the polyaluminum sample to be tested, add 0.5 mL of nitric acid solution and make the volume to 50 mL, test under the 308.215 nm characteristic spectrum of ICP-OES, substitute the tested intensity value into the standard curve obtained by ICP-OES, and calculate the aluminum content.
[0055] The results are shown in Table 1 below:
[0056] Table 1 Measurement results of polyaluminum content in comparative examples and embodiments
[0057]
[0058] Comparative Example 1 is a test of aluminum content in a polyaluminum solution, mainly to examine the comparison of test data between the spectrophotometer method selected in the present invention and the instrumental method using the precision instrument ICP-OES and the accuracy comparison of the spectrophotometer method. The embodiment mainly examines the accuracy of the detection method of the present invention.
[0059] As can be seen from Table 1, the selected spectrophotometer method for detecting the aluminum content in the polyaluminum flocculant is basically consistent with the test value using large-scale precision instruments, the spiked recovery rate is greater than 99%, and the accuracy is high. Example 1 and Example 2 show that the patented method can accurately measure the polyaluminum content in machine-made sand. Combining the actual use of the mixing station and the test results, it is further shown that the machine-made sand contains polyaluminum flocculants. The residual polyaluminum flocculants in the machine-made sand induce problems such as high admixture dosage in concrete and large loss of workability. Experimental results show that the detection method can effectively detect residual polyaluminum flocculants in machine-made sand, effectively improving the control of raw materials of concrete production enterprises.
[0060] Figure 1 This is the aluminum content-absorbance standard curve established by the spectrophotometer in the present invention. According to the standard curve, a linear regression equation Y=0.00433*X+0.10575, R2=0.999 is established. Figure 2 The present invention uses a large precision instrument ICP-OES as the aluminum content-absorbance standard curve for comparison of the method of the present invention, and a linear regression equation standard curve is established based on the curve: Y=2414.89*X+0.15189, R2=0.999. As can be seen from the figure, the detection value of the method of the present invention is less than 3% of the ICP-OES test value, and the spike recovery rate is greater than 99%, and the method has high accuracy.
[0061] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A rapid detection method for the residual amount of polyaluminum type flocculant in machine-made sand, characterized in that: The detection steps include the following:
1. Preparation of test solution Dry the machine-made sand sample, add deionized water and stir to make it completely wet, then add sodium hydroxide, heat to 60~100℃ and cook for 1~2 hours, add more sodium hydroxide and cook until there is no white floc in the solution, then cool to room temperature, centrifuge, filter, wash several times, take out the filtrate and add inorganic acid until the solution becomes transparent, then add water to dilute and fix the volume to obtain the solution to be tested; 2. Establish a standard curve S1. Weigh different masses of standard aluminum solution into a conical flask, add acid-base indicator and inorganic acid to adjust the pH to acidic, then add buffer solution, emulsifying solution, masking agent, and color developer, dilute to 50 mL with water, mix well, heat to boil, and then cool to room temperature; S2, introducing the standard aluminum solution treated by S1 into the UV spectrophotometer through the sampling system for testing, measuring the absorbance of the solution with the actual blank as a reference, and drawing a standard curve of aluminum content and absorbance; S3, establishing a standard curve equation based on the standard curve of aluminum content and absorbance drawn in S2; 3. Test sample solution S1. Weigh the sample solution ag into a conical flask, add acid-base indicator and inorganic acid to adjust the pH to acidic, then add buffer solution, emulsifying solution, masking agent, and color developer, dilute to 50 mL with water, mix well, heat to boil, and then cool to room temperature; S2, introducing the polyaluminium solution sample to be tested into the UV spectrophotometer through the sampling system, and performing the test, substituting the absorbance of the polyaluminium solution sample to be tested into the standard curve equation established in step 2 S3, and calculating the aluminium content in the sample to be tested; The inorganic acid selected in the test solution is one of sulfuric acid, nitric acid, and hydrochloric acid, or a mixture of two or more in any proportion, and the concentration of the inorganic acid solution is 10 mol / L; The buffer solution is composed of one or two of sodium acetate-acetic acid and ammonium acetate-acetic acid; The emulsified solution is composed of one or more of OP-3, OP-10 and lauryl alcohol polyoxyethylene ether, and the addition amount thereof is 0.1% to 3% of the total mass; The masking agent is one or more of ascorbic acid, citric acid, mandelic acid, and o-phenanthroline; The main component of the developer is aluminum reagent, i.e., tricarboxyammonium salt of golden yellow pigment, with the molecular formula of C22H23N3O9; The detection wavelength range of the ultraviolet spectrophotometer is 400-600 nm.
Citation Information
Patent Citations
Method for detecting flocculant in sand and detecting device thereof
CN110261265A
Method for detecting polyacrylamide in machine-made sand
CN113030447A
On-line detection and evaluation method for flocculation effect of flocculant based on spectrophotometer
CN108007879A
Rapid determination method of cross-linked sodium hyaluronate gel protein residues
CN112147095A
Cited By
Method for testing content of flocculant in machine-made sand
CN117664794A